Opportunities of agency in determining deduction of customs value - Bankovičs, Kārlis (Riga Graduate School of Law, 2018)
This paper examines the agent`s importance in international trade regarding the deduction of customs value. The conclusion of the research confirmed that there is a legal basis for computing deduction on the customs value when the buyer`s agent is involved in the expenses of goods transportation and insurance. The buyer`s agent can be beneficial for the principal by taking the costs of transportation and insurance on himself thus resulting in smaller customs valuation. Therefore, smaller amount of taxes will be applicable to the goods imported resulting in less amount paid in taxes. In addition, another conclusion was made that each state has too much power to dictate the agency laws thus it makes confusion and fragmented laws on the international level.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International private law and international procedural law; International trade